ANALISIS SISTEM PENGENDALIAN INTERNAL SIKLUS PENGGAJIAN PADA PT. GOSEPA TOUR & TRAVEL - RATNA SARI, DWI Ratna (Jurnal Akuntansi AKUNESA, 2013)
This research are doing on PT. Gosepa Tour&Travel. Interrnal control system ofpayroll cycle is necessary for prevent the possibility of fraud ythe might happen. The purposeof this research for knowing the organitation structure internal control system on PT. GosepaTour&Travel. The methode of this research using descriftif-kualitatif. With result thatinternal control system on PT. Gosepa Tour&Travel going on very well. This can be seenfrom job separation and responsibilities in organization structure. System of otoritation andrecording procedures are good. And also the implementation of healthy practices in carryingout their respective duties of each section.Keyword: Internal control system, payroll cycle, fraud